The Influence of Hoaxes on Voter Participation from a Civic Education Perspective in Indonesia - Khaz, Fitra Hadi; Arsyika, Nadhra; Habibi, Jefri Nur; Sari, Indah Jelita; Effendi, Frya Destra (Civiliza Publishing, Indonesia., 2025)
The development of information technology and the dominance of social media in public life have changed the patterns of dissemination and consumption of political information, while simultaneously increasing the intensity of the spread of hoaxes. This phenomenon has the potential to influence public perceptions, attitudes, and political participation in elections. This study aims to examine the influence of the spread of hoaxes on voter participation in elections in Indonesia, both in terms of turnout and the quality of political participation. The research method used is qualitative with a descriptive analytical approach through a library study of relevant literature, institutional reports, and scientific journals. The research analysis utilizes Agenda Setting Theory to explain the role of the media, particularly social media, in shaping issues deemed important by the public. The results show that social media, particularly Facebook and WhatsApp, have become primary loci for the spread of political hoaxes due to their gatekeeper-free nature, virality-based nature, and the support of algorithms that amplify polarization and echo chambers. Therefore, strengthening digital literacy, political education, and fact-checking practices are essential prerequisites for maintaining the quality of voter participation and the sustainability of democracy in Indonesia.